Effect of Compensation, Spirit at work and Communication On Employee Performance - Khoirul Abidin; Budi Prayitno; Sarah Yuliarini (Antis Publisher, 2024)
This research aims to determine the effect of compensation, work morale, communication on employee performance at REM.Company with a quantitative research method using SPSS statistical data, data was taken based on a questionnaire with likert scale calculations given to 48 REM Company employees and the research results can be processed to show that the Compensation variable has a significant effect on Employee Performance. Spirit at Work has a significant effect on Employee Performance. Communication has a significant effect on employee performance. Communication has a significant effect on employee performance.